Assessment of pembrolizumab exposure in different patient subpopulations using pharmacometric simulation - Homšek, Ana; Jovanović, Marija; Miljković, Branislava; Vučićević, Katarina (Archives of Pharmacy, 2022)
Monoclonal antibodies’ pharmacokinetics is, due to their specific properties, highly variable among different patients. Beside body weight and albumin levels, pembrolizumab pharmacokinetics may also be affected by patient's condition depicted as ECOG (Eastern Cooperative Oncology Group) performance status and tumor burden. The study aim was to compare pembrolizumab exposure in different patient subpopulations after administration of fixed (200 mg) and weight-based dosing regimen (2 mg/kg) every three weeks. Two virtual populations were generated in the R software: normal body weight patients with preserved renal function, normal albumin levels (3.4-5.8 g/dL) and good prognosis (ECOG 0, low burden); and underweight patients with decreased renal function, hypoalbuminemia (